The Relationship Between Learning Styles with Learning Outcome and Scientific Literacy of Islamic Junior High School (MTs) Students in Mataram - Nufus, Siti Syifa’un; Hadiprayitno, Gito; Jufri, A Wahab (Jurnal Ilmiah Mandala Education (JIME), 2021)
Learning style is one of the important elements in the learning process of students. Information about student learning styles will help teachers design appropriate learning so that students can more easily absorb, organize, and process information during the learning process. Learning in accordance with the character of students in the class will create joyful learning and influences student learning outcomes and abilities, including scientific literacy. This study aims to investigate the relationship between learning styles with student learning outcomes and scientific literacy. This research is descriptive-experimental research. The population of this study was MTs students in Mataram and the subjects of this study were 55 students. In order to determine the tendency of student learning styles, the VARK learning style questionnaire (Visual, Auditory, Read/Write, and Kinesthetic) was developed. In order to assess the scientific literacy that consisted of scientific literacy multiple-choice test and to assess the learning outcome, the final score was employed. Analysis of the relationship between learning styles and the scientific literacy using bivariate correlation, while the effect analysis of learning styles on learning outcomes and scientific literacy using MANOVA and effect analysis of students' scientific literacy on learning outcomes using ANACOVA. The results of the study indicated that the trend of auditory and kinesthetic learning styles correlated significantly with students' scientific literacy (p <0.05), whereas visual and reading/writing learning styles did not significantly correlate (p> 0.05). The type of learning styles does not have a different effect on student learning outcomes and scientific literacy, but scientific literacy has a significant influence on learning outcomes (p <0.05).